Neglected venomous animals and toxins: Underrated biotechnological tools in drug development - Coelho, Guilherme Rabelo; da Silva, Daiane Laise; Beraldo-Neto, Emidio; Vigerelli, Hugo; de Oliveira, Laudiceia Alves [UNESP]; Sciani, Juliana Mozer; Pimenta, Daniel Carvalho (MDPI, 2021)
Among the vast repertoire of animal toxins and venoms selected by nature and evolution, mankind opted to devote its scientific attention—during the last century—to a restricted group of animals, leaving a myriad of toxic creatures aside. There are several underlying and justifiable reasons for this, which include dealing with the public health problems caused by envenoming by such animals. However, these studies became saturated and gave rise to a whole group of animals that become neglected regarding their venoms and secretions. This repertoire of unexplored toxins and venoms bears biotechnological potential, including the development of new technologies, therapeutic agents and diagnostic tools and must, therefore, be assessed. In this review, we will approach such topics through an interconnected historical and scientific perspective that will bring up the major discoveries and innovations in toxinology, achieved by researchers from the Butantan Institute and others, and describe some of the major research outcomes from the study of these neglected animals.
Keywords: Drug discovery; Skin secretion; Toxins; Venoms